Physical and Emotional Burden on Patients Receiving Intravitreal Administration of Bevacizumab - Shrestha, Abishek; Shakya, Sangita; Shakya, Kiran (Journal of Advanced Academic Research, 2026)
Background:Bevacizumab is intravitreally administered for wide range of vision-threatening retinal diseases.The treatment is effective in stabilizing vision, however repeated injections may impose physical discomfort, emotional stress, and restrictions in daily life and this overall affects quality of life of patients. Evidence on these outcomes in the Nepalese context is very limited.Objective:To determine physical and emotional burden on patients receiving intravitreal administration of bevacizumab.Research Methodology: A cross-sectional, hospital-based descriptive study was conducted at Tertiary Eye Hospital from October to December 2024. A total of 54 patients were included. Data were collected using a validated, questionnaire adapted from the QUALITII tool, covering physical and emotional burden factors.Results: Physically, 66.67% of patients reported pain during injection and the most common side effects were eye pain (61.1%), light sensitivity (46.3%), and floaters (25.9%).  61.1% of patients reported restrictions on daily activities after injection. Emotionally, anxiety decreased significantly after treatment, which indicates patients feeling more relieved after the injection.Conclusion: Intravitreal bevacizumab therapy imposes considerable physical and emotional burdens. Addressing pain management and counselling is essential to improve overall patient wellbeing and adherence.